Synthesis of titanates for photomineralization of industrial wastewater and organic pollutants. Issue 12 (27th October 2022) - Gade, Ramesh; Basude, Manohar; Simhachalam, Narendra Babu; V, Rama Devi; Pola, Someshwar; Chetti, Prabhakar
Abstract : The optical parameters of tunnel type titanates NaTO, PdTO and Ag/PdTO were studied and they were used as photocatalysts for the photomineralization of various organic dye pollutants and industrial wastewater (IWW) under visible light irradiation. Abstract : In the current study, a tunnel-type titanate nanomaterial (Na2 Ti3 O7, NaTO) was converted into PdTi3 O7 (PdTO) through an ultrasonication-assisted ion-exchange method. Ag nanoparticles were then deposited on the surface of PdTO through sonication to give Ag/PdTO, which exhibited improved visible-light-induced photocatalytic activity. The composition and phase of each nanomaterial were examined by X-ray photoelectron spectroscopy, powder X-ray diffraction, and various spectroscopic techniques. Using estimates from spectrophotometry and the solution of the radiative transfer equation, the optical parameters of these titanates (NaTO, PdTO, and Ag/PdTO) were reported. The specific scattering and absorption coefficients, along with the scattering phase function, were observed in the wavelength range from 250 to 650 nm. The low bandgap of Ag/PdTO, 2.42 eV, is responsible for the capture of photons of visible light for improved photomineralization of various dyes. Under the optimal settings, the photocatalytic mineralization efficacies of the dyes with Ag/PdTO and PdTO retained 98% and 60% of their starting activities after 60 min, respectively. Mechanistic studies were also conducted to understand the generation of superoxide, which is the active species in the mineralization of industrial and automobile industrial wastewater. The high photocatalytic efficiency of the Ag/PdTO system is reported.